2008
DOI: 10.1158/1535-7163.mct-08-0476
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of a polymeric nanoparticle platform with potential oral drug delivery capabilities

Abstract: Nanotechnology has enabled significant advances in the areas of cancer diagnosis and therapy. The field of drug delivery is a sterling example, with nanoparticles being increasingly used for generating therapeutic formulations of poorly water-soluble, yet potent anticancer drugs. Whereas a number of nanoparticle-drug combinations are at various stages of preclinical or clinical assessment, the overwhelming majorities of such systems are injectable formulations and are incapable of being partaken orally. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 47 publications
0
35
0
1
Order By: Relevance
“…Though a number of nanoparticle-drug combinations are assessed in preclinical or clinical applications, most of delivery systems are intravenously injectable formulations and are incapable of oral administration [17,18]. On the other hand, it has been reported that nanocomposites such as silver nanoparticle for therapeutics itself exhibits the undesired toxicity on the GI tract after repeated oral administration [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Though a number of nanoparticle-drug combinations are assessed in preclinical or clinical applications, most of delivery systems are intravenously injectable formulations and are incapable of oral administration [17,18]. On the other hand, it has been reported that nanocomposites such as silver nanoparticle for therapeutics itself exhibits the undesired toxicity on the GI tract after repeated oral administration [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It was reviewed that polymeric nanoparticles prevent inactivation and degradation caused by acidic pH and digestive enzymes [57]. A nanoparticle adheres to the mucosa and thus enhances the absorption of the associated drug [63]. Neonatal Fc receptor present in the small intestine and colon is the target for nanoparticles [64].…”
Section: For Oral Drug Deliverymentioning
confidence: 99%
“…Os primeiros medicamentos injetáveis comercializados na forma de microesferas foram o Parlodel ® LAR e o Sandostatin ® LAR (laboratório Sandoz), ambos baseados em matrizes de PLGA [122] . As nanopartículas poliméricas -nanocápsulas e nanoesferas -são sistemas que apresentam aplicações promissoras, principalmente, na vetorização de anticancerígenos, proteínas, peptídeos, vacinas tumorais e material para terapia gênica administrados pela via parenteral e, também, administração de antibióticos pela via oral [123][124][125][126] . Os principais polímeros empregados na preparação de nanocarreadores são os naturais modificados, derivados da albumina, colágeno, ácido hialurônico, gelatina, quitosana e alginato, além dos polímeros sintéticos PHEMA, PVA, PAA, PEVA, PEG e a poli(acrilamida).…”
Section: Medicamentos De Desempenho Terapêutico Avançadounclassified